Deformation and Fault Propagation at the Lateral Termination of a Subduction Zone: The Alfeo Fault System in the Calabrian Arc, Southern Italy - Maesano, Francesco Emanuele; Tiberti, Mara Monica; Basili, Roberto (Frontiers in Earth Science, 2020)
The Calabrian Arc subduction, southern Italy, is a critical structural element in the geodynamic evolution of the central Mediterranean basin. It is a narrow, northwest-dipping slab bordered to the southwest by the Alfeo Fault System (AFS) and to the northeast by a gradual transition to a collision. We used a dense set of two-dimensional high-penetration (up to 12 s) multichannel seismic reflection profiles to build a three-dimensional model that spans the AFS for over 180 km of its length. We find that the AFS is made up of four deep-seated major blind segments that cut through the lower plate, offset the subduction interface, and only partially propagate upward across the accretionary wedge in the upper plate. These faults evolve with a scissor-like mechanism (mode III of rupture propagation). The shallow part of the accretionary wedge is affected by secondary deformation features well aligned with the AFS at depth but also mechanically decoupled from it. Despite the decoupling, the syn-tectonic Pliocene-Holocene deposits that fill in the accommodation space generated by the AFS activity at depth, constrain the age of inception of the AFS and allows us to estimate its throw and propagation rates. The maximum throw value is 6,000 m in the NW sector and decreases to the SE. Considering the age of faulting, the fault throw rate decreases accordingly from 2.31 mm/yr to 1 mm/yr. The propagation rate decreases from 62 mm/yr to 15 mm/yr during the Pliocene-Pleistocene, suggesting that also the Calabrian subduction process should have slowed down accordingly. The detailed spatial and temporal reconstruction of this type of faults can reveal necessary information about the evolution of subduction systems.